Algunas consideraciones críticas sobre los viajes de Eudoxo de Cícico - Albaladejo Vivero, Manuel (Gerión. Revista de Historia Antigua, 2008)
The story about the travels to India supposedly undertaken by Eudoxus of Cyzicus has been kept remained in the work of Strabo, who grounded it on the writings of Posidonius. The tone of this story appears to me as not very realistic. In comparison with the news written by Cornelius Nepos, we clearly see paradoxographical aspects. They are, of course, literary ones. All this topics are included within the framework of the Hellenistic discussion on geographical questions, being one of the favourite the possible navigation around Africa.